MORAL CLUMSINESS. Issue 40 (9th April 2015) - Arango, Alejandro
Abstract : What would happen if one morning you wake up clumsy, as if your sense of touch were unreliable, arbitrarily on and off? And what would this clumsiness look like if we could transfer it to the moral sense? The article expounds an interesting analogy between the sense of touch, loosely construed, and the moral sense: just as a sort of consistency is necessary for the sense of touch to do its job, so it is for the moral sense to play its part. Touch enables us to navigate the everyday world of coffee pots and staircases; our moral sensibility comes into play when we act or when we judge our actions and those of others, and plays a directive role in what we feel, how we feel it, and how we react to it. Taking the analogy further, I will suggest that inconsistency causes, in both cases, a certain clumsiness, and that clumsiness is linked to arbitrariness – like the person that helps others in dire need, but only does so on some rainy days.